Are US family firms subject to agency problems? Evidence from CEO turnover and firm valuation - CHEN, Xia (Institutional Knowledge at Singapore Management University, 2007)
This paper investigates the impact of the founding family's presence in US public firms on the extent of agency problems related to CEO turnover decisions and on firm valuations after poor performance. In particular, we focus on three types of US public firms: family CEO firms, professional CEO family firms (family firms managed by a hired CEO outside the founding family), and non-family firms. We hypothesize that, the agency problem arising from the expropriation of small shareholders by large shareholders in family CEO firms and the agency problem arising from the separation of ownership and control in non-family firms, lead to a lower CEO turnover-performance sensitivity, compared to professional CEO family firms. Professional CEO family firms are subject to lesser agency problems due to the separation of family ownership and management as well as the founding family's effective monitoring of management. The empirical findings are consistent with our prediction. We further hypothesize and find that the more severe agency problems in both family CEO firms and non-family firms manifest themselves in lower firm value after poor performance, relative to professional CEO family firms. Overall, our results indicate that in the CEO turnover setting, family ownership, when separated from management, can mitigate agency problems as in professional CEO family firm, but when combined with management, can aggravate agency problems as in family CEO firms.